Supporting a Strong Start: Using Universal Vital Records to Understand the Service Needs of Newborns and their Families - Foust, Regan; Putnam-Hornstein, Emily; Prindle, John (International Journal of Population Data Science, 2024)
The [Index] is a simple, yet innovative, tool that makes better use of data routinely collected at birth to summarize the assets that exist across and within communities. Comprising 12 health, family, and financial indicators available on standard birth records, the Index offers a strengths-based, cost-effective, holistic, valid, and meaningful characterization of the conditions into which newborns are born at both a state and local level. Given the strong, graded relationship between [Index] scores and the predicted probability of child protection involvement and death before age 5, the Index has become an important tool among policymakers to identify communities who should be prioritized for investment so that supports can be allocated more equitably and earlier in children’s lives. It also has provided an opportunity to develop a representative sample of children born into families with historically high service needs, but low engagement, to whom we would reach out directly to gather their perspectives of service experiences. This information will be augmented with administrative records as children age. This work will fill a major gap in information about the needs and experiences of the entire population of young children and families – not just those who engage in services – and the barriers, benefits, and challenges new parents may face in accessing the supports they need. This session will highlight the [Index], its relationship to child-level outcomes, how communities are using it to facilitate equitable investment, and, given international birth record standardization, how other jurisdictions might implement a similar tool.